KERJASAMA GURU DAN KEPALA SEKOLAH DALAM MENANAMKAN NILAI AKHLAK KEPADA SISWA DI SEKOLAH DASAR NEGERI 7 SASAK KECAMATAN SAJINGAN BESAR - Norida Norida (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
The purpose of this study is to reveal about: 1) The form of collaboration between teachers and school principals to instill moral values ​​in students of SD Negeri 7 Sasak, Sajingan Besar District, in the 2019/2020 school year; 2) How teachers and principals instill moral values ​​in students at SD Negeri 7 Sasak, Sajingan Besar District, Academic Year 2019/2020. This research uses a qualitative approach and type of case study research. The research subjects were classroom teachers and school principals. Data collection techniques using interview methods, observation and documentation. To arrive at the data analysis the researchers used consisted of data collection, data reduction, data display, verification and conclusion drawing. The results showed that: 1. The form of collaboration between teachers and school principals instilling moral values ​​in students of SD Negeri 7 Sasak, Sajingan Besar District, the 2019/2020 school year consists of several steps, namely: 1) Involving teachers in improving student quality; 2) Involving educators (teachers) in activities, 3) Involving teachers in Seminars, MGMP, Cluster Deliberations, Teaching Training. 2. How teachers and principals instill moral values ​​in students at SD Negeri 7 Sasak, Sajingan Besar District, Academic Year 2019/2020, namely: 1) Conducting Formative Assessments; 2) Give attention; 3) Provide guidance; and 4) Set an example.